(untitled) (Bangladesh Journal of Zoology, 2021)
The study was conducted to identify the protozoan parasites in a freshwater indigenous air breathing fish, Anabas testudineus. The host fish was collected during mid of the April 2018 to end of the March 2019 from freshwater bodies of Mymensingh, Kishoregonj, Faridpur, Jashore, Manikganj and Bogura districts of Bangladesh. Five species of phylum myxozoa namely Henneguya gigas, Henneguya mystusia, Henneguyaa cerinae, Henneguya periophthalmusi and Myxidium sp., three species of phylum ciliophora namely Amphileptus disciformis, Epistylisl woffi and Trichodina anabasi and one species of phylum mastigophora namely Trypanosoma anabasi were identified in A. testudineus. Myxozoans (97.55%) were clearly dominant group than chiliophorans (2.45%). Bangladesh J. Zool. 49 (2): 331-345, 2021